MISE EN SCENE PROGRAM JAGONGAN SAR GEDHE DAN PEMAKNAANNYA - Citra Ratna Amelia; D., Dharsono (Institut Seni Indonesia Surakarta, 2016)
Artikel ini merupakan hasil dari penelitian yang ingin mengungkapkan makna yang terkandung dalam mise en scene program Jagongan Sar Gedhe. Permasalahan yang dikaji dalam penelitian ini diantaranya adalahbagaimana latar belakang penciptaan program Jagongan Sar Gedhe?, bagaimana mise en scene program Jagongan Sar Gedhe? Bagaimana makna yang terkandung dalam mise en scene program Jagongan SarGedhe?.Penelitian ini menggunakan pendekatan semiotik Roland Barthes dengan melakukan pendekatan signifikansi dua tahap, yaitu tahap denotatif dan konotatif terhadap mise en scene program Jagongan Sar Gedhe. Hasil penelitian ini diantaranya: program Jagongan Sar Gedhe diciptakan sebagai sebuah wadahkomunikasi dan wadah pengkritisan bagi para pemangku kebijakan. Budaya lokal disisipkan dalam unsur mise en scene program Jagongan Sar Gedhe, di mana setting yang digunakan menggunakan ikon pasar Gede sebagai background, setting tempat duduk dibuat lesehan dengan menambahkan gerobak HIK dan alat musik gamelan sebagai backdropnya, kostum yang digunakan para pengisi acara antara lain kemeja batik, lurik, dan kebaya dengan tata rias yang natural. Makna dalam unsur mise en scene program Jagongan Sar Gedhe antara lain makna kebebasan berdemokrasi dan toleransi, makna keegaliteran, makna kesederhanaan dan keakraban, serta makna harmoni.Kata Kunci: Mise En Scene, Program Jagongan Sar Gedhe.The article constitutes a research finding trying to reveal the meaning contained in mise en scene of the program Jagongan sar Gedhe. The problem studied in the research includes how the background of creating the program Jagongan sar Gedhe is, how mise en scenein Jagongan Sar Gedhe is, and how the meaningcontained in mise en scene of program Jagongan Sar Gedhe is. This research applies semiotic approach of Roland Barthes by conducting two stages of significant approach including denotative and connotative stagestowards mise en scene in program Jagongan Sar Gedhe. The research finding shows that program Jagongan Sar Gedhe is created as a media of communication and criticizing the decision makers. Local culture is inserted in mise en scene of program Jagongan Sar Gedhe where the setting uses the icon of Pasar Gedhe as background. The seat setting is lesehan (sits at plaited mat or floor) added by a cart of HIK and gamelan instruments as backdrop. The costumes used by the event participants among other things are batik, lurik(cloth with small line motive), and kebaya (usually worn with a sarong) with natural make up. The meaning of elements in mise en scene program Jagongan Sar Gedhe covering the meaning of freedom of democracy and tolerance, the meaning of egalitarian, simplicity and intimacy, and also the meaning of harmony.Keywords: Mise En Scene, program Jagongan Sar Gedhe.